2019
DOI: 10.1007/s13593-019-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

Top-down suppression of arthropod herbivory in intercropped maize and organic farms evidenced from δ13C and δ15N stable isotope analyses

Abstract: Maize is a globally important cereal crop and a staple in sub-Saharan Africa, where it is predominantly grown by small-scale farmers. Its production, however, is undermined by numerous herbivorous arthropods, and agrochemicals used for controlling such pests are increasingly unaffordable. Farmers therefore require cheaper, effective and environmentally sustainable pest management alternatives. This study explored the hypothesis that boosting habitat heterogeneity through organic farming and intercropping enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This implies the possibility that plants in push-pull soil may constitutively attract natural enemies of herbivores into the crop plant population and so mediate constitutive indirect resistance. Previous studies have shown that intercropping systems are associated with higher natural enemy numbers of herbivores and play a role in reducing herbivore numbers in these systems through predation and increased parasitism ( Otieno et al, 2019;Khan et al, 1997). In our study, we suggest intercrop-induced VOC emission as a new mechanism for increased pest control in intercropping systems in general and push-pull in particular.…”
Section: Discussionsupporting
confidence: 51%
“…This implies the possibility that plants in push-pull soil may constitutively attract natural enemies of herbivores into the crop plant population and so mediate constitutive indirect resistance. Previous studies have shown that intercropping systems are associated with higher natural enemy numbers of herbivores and play a role in reducing herbivore numbers in these systems through predation and increased parasitism ( Otieno et al, 2019;Khan et al, 1997). In our study, we suggest intercrop-induced VOC emission as a new mechanism for increased pest control in intercropping systems in general and push-pull in particular.…”
Section: Discussionsupporting
confidence: 51%
“…Except from the last two and a half decades when official forest protection enforcement began to improve, the trends in forest's destruction, degradation, and fragmentation had traditionally been tied to the fact that it is surrounded by farmland and a dense human population practicing mainly subsistence agriculture and small-scale livestock husbandry but with considerable dependence on the forest for wood, fiber, and other products, though this is now regulated by forest management authorities (Farwig et al, 2008). The main crop on the eastern side of the forest includes mainly non-Bt maize, which is commonly intercropped with legume crops (Otieno et al, 2019a). Farmers also typically maintain some stand of woodlots and fruit orchards, and also plant trees along property boundaries, and occasionally establish fast-growing agroforestry trees alongside row-crops (Diwani et al, 2013).…”
Section: Study Areamentioning
confidence: 99%
“…From the perspective of spatial and temporal fluxes in resource abundance such as the cycles of crop planting seasons followed by after-harvest transitions, such taxon-level food resource diversification and flexibility are important for the herbivores' survival and persistence (Driscoll et al, 2013). However, the herbivores 'apparent overall preference of maize over the other two plant food sources likely owed to the position of maize as the predominant and most abundant subsistence row-crop, as well as being the most common across these particular farming landscapes (Laube et al, 2008;Otieno et al, 2019a) For this reason. therefore, of the three plant food options assessed here, maize was the most readily available to most herbivorous species of the three arthropod taxa.…”
Section: Plant Food Sources In Arthropod Pest Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…By providing resources such as nectar, pollen, and habitat, intercropped flowers may increase the diversity and abundance of the natural enemies of various pest species. 8,9 This has been shown to be an effective, ecology-based method of both attracting the natural enemies of pest species and repelling pest insects in some cropping systems. [10][11][12] An intercrop of particular interest in the control of D. suzukii is sweet alyssum (Lobularia maritima).…”
Section: Introductionmentioning
confidence: 99%